Acceptance and Commitment Therapy in the Treatment of Depression Related to Military Sexual Trauma in a Woman Veteran: A Case Study. (February 2016) - Hiraoka, Regina; Cook, Andrew J.; Bivona, Jenny M.; Meyer, Eric C.; Morissette, Sandra B.
Depression is commonly reported by Veterans who have experienced military sexual trauma (MST). An increasing body of literature supports the use of Acceptance and Commitment Therapy (ACT) for the treatment of depression among civilians and military Veterans; however, additional research is needed, particularly among people exposed to trauma. This clinical case study describes the application of ACT with a 21-year-old woman Veteran who sought treatment for depression related to MST. The Veteran's depression symptoms decreased substantially over the course of therapy. Moreover, she demonstrated increased ability to attend to the present moment, tolerate feelings of uncertainty, and make decisions consistent with her chosen values. Treatment implications of these findings are discussed, with an emphasis on the unique aspects of using ACT in the treatment of MST-related depression among Veterans.